Вдосконалення системи маркетингових досліджень на підприємстві - Семенчук, Тетяна Юріївна; Верютіна, Марія Михайлівна; Ткачова, Надія Петрівна (НТУ "ХПІ", 2017)
Маркетингові дослідження – збір, опрацьовування й аналіз інформації та можливостей, розроблення рекомендацій на підставі цих даних. Розглянуто поняття "маркетингові дослідження", визначено загальні недоліки в організації маркетингової діяльності. Досліджено комплекс маркетингових заходів підприємства, спрямований на підвищення обсягу продажів продукції підприємства. Проаналізовано узагальнення особливостей організації маркетингових досліджень та розвиток пропозицій щодо вдосконалення проведення маркетингових досліджень.

Marketing research – collecting, processing and analyzing information and opportunities, developing recommendations based on these data. The concept of marketing research determines the general shortcomings in the organization of marketing activities. The complex of marketing measures of the enterprise is aimed at increasing the sales volume of the company's products. The generalization of the peculiarities of the organization of marketing researches and the development of proposals for improving marketing research is analyzed. The system of marketing researches was analyzed on the example of Kharkiv enterprise of plug-in connectors. The peculiarities of organization of marketing researches at the enterprise are analyzed. IdentifiedReveloping proposals for improving marketing research. The directions of marketing research are determined.
Improvement of the system of marketing researches at the enterprise
Keywords: маркетинг; підприємство; стимулювання збуту; ринок; marketing; enterprise; sales promotion; market